2023
DOI: 10.2147/jmdh.s405509
|View full text |Cite
|
Sign up to set email alerts
|

Acne Vulgaris Relapse in Sudanese Patients Treated with Oral Isotretinoin: Rate and Predictive Factors

Abstract: Purpose Acne vulgaris is a skin disorder primarily affecting teenagers and young adults. Acne relapse is the main drawback of oral isotretinoin (OI), which is the golden therapy for severe acne. This study aimed to assess the rate and predictive factors of acne relapse among Sudanese patients using OI. Patients and Methods A cross-sectional study was conducted in a dermatology and venereology clinic-Sudan, using a self-administered questionnaire and data collection shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(88 reference statements)
0
0
0
Order By: Relevance
“…Tolino, et al, conducted an observational study and reported excellent results in the treatment of moderate acne with oral (systemic) isotretinoin, with higher effectiveness and less recurrence risk [31]. However, Ibrahim, et al, found that approximately 36% of patients experienced acne relapse at the 2-year follow-up, with early discontinuation of isotretinoin treatment being a positive predictor of relapse [33]. These findings suggest that oral (systemic) isotretinoin is effective in treating acne, but completion of the planned course of treatment and long-term therapy may be necessary to reduce relapse rates.…”
Section: Efficacy Of Topical Isotretinoin Vs Oral (Systemic) Isotreti...mentioning
confidence: 99%
“…Tolino, et al, conducted an observational study and reported excellent results in the treatment of moderate acne with oral (systemic) isotretinoin, with higher effectiveness and less recurrence risk [31]. However, Ibrahim, et al, found that approximately 36% of patients experienced acne relapse at the 2-year follow-up, with early discontinuation of isotretinoin treatment being a positive predictor of relapse [33]. These findings suggest that oral (systemic) isotretinoin is effective in treating acne, but completion of the planned course of treatment and long-term therapy may be necessary to reduce relapse rates.…”
Section: Efficacy Of Topical Isotretinoin Vs Oral (Systemic) Isotreti...mentioning
confidence: 99%